Y2O3-Doped BioGlass Coatings for Ti-6Al-4V Alloy: Insights into Degradation, Bioactivity, Ion Release, Adhesion, and Corrosion Behavior - Say, Yakup; Aslan, Naim; Cihangir, Salih; Murat, Oguzkagan; Caydas, Ulas (Springer, 2025)
The Ti-6Al-4V alloy is particularly favored for orthopedic applications. However, important issues such as corrosion resistance, biocompatibility, and ion release need to be addressed. Therefore, this study aims to enhance the corrosion resistance and biocompatibility and reduce the ion release of the Ti-6Al-4V alloy by applying Y2O3-doped bioglass bioceramic coatings. The coatings were synthesized using the sol-gel method, including pure BioGlass and BioGlass with 1, 5, and 10 wt pct Y2O3. These coatings were then evaluated for their corrosion resistance, adhesion strength, degradation behavior, bioactivity, and ion release. The results showed that all coatings exhibited homogeneous, crack-free, and porous morphologies, which are favorable for osteointegration. The addition of 10 wt pct Y2O3 to the BioGlass coating resulted in a 52 pct increment in adhesion strength, which increased from 13.72 +/- 2.80 MPa for single BioGlass coatings to 20.81 +/- 2.53 MPa. All samples showed degradation values lower than 1 wt pct. Single BioGlass coatings significantly enhanced the bioactivity of Ti-6Al-4V alloy. However, the addition of Y2O3 negatively impacted BioGlass bioactivity, leading to a noticeable decrease as the Y2O3 content increased. Conversely, the presence of Y2O3 negatively impacted bioactivity and corrosion resistance while increasing the release of Ti ions. Specifically, the release of Ti ions increased from 79.5 +/- 0.8 ppb in uncoated samples to 253.7 +/- 15.3 ppb in BG-coated samples. For 1, 5, and 10 pct Y2O3-added samples, Ti releases were measured as 192.2 +/- 33.6 ppb, 168.5 +/- 62.4 ppb, and 194.3 +/- 54.4 ppb, respectively. This research highlights the potential of tailored BioGlass coatings to improve the performance of Ti-6Al-4V alloys in orthopedic implant applications, particularly for enhancing bone integration and reducing implant failure.
Keywords: In-Vivo; Hydroxyapatite; Glass; Titanium; Microstructure; Resistance; Metals